LINGUISTIC AND PRAGMATIC ANALYSIS OF THE FUNCTIONING OF PRAGRAMATIC MARKERS IN ENGLISH AND GEORGIAN FORENSICS: Based on courtroom discourse - Gvritishvili, Sophie (Online Journal of Humanities ETAGTSU, 2020)
This article discusses the findings of a contrastive study of pragmatic markers as indicators of illocutionary force based on the compatible data from English and Georgian languages. As is known, discourse markers are commonly used in everyday communication. They are important indicators concerning the portraying a speaker’s intentions and attach certain force to the utterances employed. This paper describes various uses of specific discourse markers as found in lawyers’ questions during the stages of direct examination and cross-examination. It is argued that such markers are used as argumentation and confrontation strategies and maintain control of the flow of information, and mark a progression in the narration. A general classification of such markers is based on Fraser’s taxonomy. <a title="Linguistic and Pragmatic Analysis of the Functioning of Pragramatic Markers in English and Georgian Forensics" href="https://etag.tsu.ge/journal/files/05_Sophie-Gvritishvili.pdf" target="_blank" rel="noopener">Full Text (PDF)